Meeting the Complex Needs of Urban Youth and Their Families Through the 4Rs 2Ss Family Strengthening Program: The "Real World" Meets Evidence-Informed Care. (July 2015) - Small, Latoya A.; Jackson, Jerrold; Gopalan, Geetha; McKay, Mary McKernan
Background: Youth living in poverty face compounding familial and environmental was challenges in utilizing effective community mental health services. Ongoing stressors increase their drop-out rate in mental health service use. Difficulties also exist in staying engaged in services when involved with the child welfare system. This study examines the 4Rs 2Ss Family Strengthening Program developed across four broad conceptual categories related to parenting skills and family processes that form a multiple family group service delivery approach. Methods: Families randomly assigned to the experimental condition received a 16-week intervention. Data was collected at baseline, midtest, posttest, and follow-up. Results: There was a higher engagement rate in the experimental condition and improved effects for child behaviors. Family stress and parental depression were also related to engagement. No moderation effects on family stress, child welfare involvement, or parental needs were found. This intervention appeared to be able to engage families with more complex "real-world" needs.